Agrowaste-generated biochar for the sustainable remediation of refractory pollutants - Ghosh, Sougata; Nandasana, Maitri; Webster, Thomas J.; Thongmee, Sirikanjana (Frontiers in Chemistry, 2023)
The rapid growth of various industries has led to a significant rise in recalcitrant pollutants in the environment at an alarming rate. Hazardous dyes, heavy metals, pesticides, pharmaceutical products, and other associated polycyclic aromatic hydrocarbons (such as acenaphthene, fluorene, fluoranthene, phenanthrene, and pyrene) have posed a significant threat to the surroundings due to their refractory nature. Although activated carbon has been reported to be an adsorbent for removing contaminants from wastewater, it has its limitations. Hence, this review gives an elaborate account of converting agricultural waste into biochar with nanotextured surfaces that can serve as low-cost adsorbents with promising pollutant removing properties. A detailed mechanism rationalized that this strategy involves the conversion of agro-waste to promising adsorbents that can be reduced, reused, and recycled. The potential of biowaste derived biochar can be exploited for developing biofuel for renewable energy and also for improving soil fertility. This strategy can provide a solution to control greenhouse gas emissions by preventing the open burning of agricultural residues in fields. Further, this serves a dual purpose for environmental remediation as well as effective management of agricultural waste rich in both organic and inorganic components that are generated during various agricultural operations. In this manner, this review provides recent advances in the use of agro-waste generated biochar for cleaning the environment.